Impact of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection and disease-2019 (COVID-19) on the quality of life of rheumatoid arthritis patients in Benin - Zomalheto, Zavier; ASSOGBA, CALIXTE; DOSSOU-YOVO, Hilaire (My University, 2020)
Aim of the work: To study the impact on the quality of life (QoL) of rheumatoid arthritis (RA) patients following up in a university hospital in Benin during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) disease 2019 (COVID-19) pandemic. Patients and methods: The QoL of 68 RA patients was assessed using Medical Outcome Study Short Form 36 (MOS-SF36) scale across the physical (PCS) and mental (MCS) components scores. The disease activity score (DAS28) was considered. Patients accepting to participate and having a mean of communication via social network, in particular WhatsApp were included. Results: The mean age of the patients was 49.9 ± 12.1 years (11–83 years) and were 65 females and 3 males. The mean DAS-28 at the start of the restriction measures was 3.4 ± 1.5, the mean PCS and MCS were 71.1 ± 20.3 and 67.1 ± 16.02 respectively and became 4.7 ± 2.04, 38.1 ± 4.96 and 36.8 ± 3.8 respectively. After 2 months, none of the RA patients presented with classic symptoms of COVID-19 infection. 8 patients were screened by Rapid Diagnostic Test and Reverse Transcription-Polymerase Chain Reaction. Only 1 case was positive but asymptomatic. All patients had altered QoL according to MOS-SF36. Factors associated with this deterioration were stress related to SARS-CoV2 isolation (p = 0.001), stress of having an activity flare-up (p = 0.001), fear of being stigmatized (p = 0.009). The economic factors were significantly associated with temporary unemployment, decrease in monthly income, and drug discontinuation (p = 0.001, p = 0.002 and p = 0.046 respectively). Conclusion: The impact of the SARS-CoV2 pandemic is negative on the QoL of RA patients and many factors were contributing
Keywords: Rheumatoid arthritis; SARS-CoV2; Pandemic; Benin